2010
DOI: 10.1186/1471-2229-10-55
|View full text |Cite
|
Sign up to set email alerts
|

A full-length enriched cDNA library and expressed sequence tag analysis of the parasitic weed, Striga hermonthica

Abstract: BackgroundThe obligate parasitic plant witchweed (Striga hermonthica) infects major cereal crops such as sorghum, maize, and millet, and is the most devastating weed pest in Africa. An understanding of the nature of its parasitism would contribute to the development of more sophisticated management methods. However, the molecular and genomic resources currently available for the study of S. hermonthica are limited.ResultsWe constructed a full-length enriched cDNA library of S. hermonthica, sequenced 37,710 clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…The currently available EST sequences in parasitic plants are still limited to several species; ESTs for three members of the Orobanchaceae family, i.e., S. hermonthica, P. aegyptiaca, and T. versicolor (Yoshida et al, 2010;Yang et al, 2014), the root parasite in Santalales, S. album (sandalwood), and the stem parasite Cuscuta pentagona (Kim et al, 2014;Ranjan et al, 2014) have been reported. The P. japonicum sequences analyzed in this study provide a valuable addition to parasitic plant gene databases and are suitable for conducting comparative analyses with other parasitic species.…”
Section: Comprehensive Survey Of Genes Involved In the Earlymentioning
confidence: 99%
See 2 more Smart Citations
“…The currently available EST sequences in parasitic plants are still limited to several species; ESTs for three members of the Orobanchaceae family, i.e., S. hermonthica, P. aegyptiaca, and T. versicolor (Yoshida et al, 2010;Yang et al, 2014), the root parasite in Santalales, S. album (sandalwood), and the stem parasite Cuscuta pentagona (Kim et al, 2014;Ranjan et al, 2014) have been reported. The P. japonicum sequences analyzed in this study provide a valuable addition to parasitic plant gene databases and are suitable for conducting comparative analyses with other parasitic species.…”
Section: Comprehensive Survey Of Genes Involved In the Earlymentioning
confidence: 99%
“…RNA was extracted using a CTAB/LiCl based-protocol as previously reported (Yoshida et al, 2010). Genomic DNA was removed from the RNA samples by treatment with DNase I, Amplification Grade (Life Technologies; Cat.…”
Section: Total Rna Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haussmann et al (2001) tested 50 sorghum varieties at two locations in both Mali and Kenya and showed that varieties having high resistance to Striga at one test location were possibly susceptible at another test location. Furthermore, Yoshida et al (2010) used SSR markers to reveal a wide genetic diversity in Striga itself. Therefore, resistant accessions identified in the present Striga resistance trial in Niger should be re-evaluated before being used as resistance source, especially in other countries than our test country Niger.…”
Section: Agro-morphological Differentiation Among the Wca Accessions mentioning
confidence: 99%
“…In addition, S. hermonthica seeds and seedlings germinated without hosts were sampled as controls. Total RNA was extracted as reported previously (Yoshida et al, 2010). For quality control of total RNAs, the 260:280 ratio (over 1.8) and the RNA integrity number (over 7) were measured by NanoDrop 1000 (Thermo Scientific) and 2100 Bioanalyzer (Agilent Technologies), respectively.…”
Section: Rna-seq Analysismentioning
confidence: 99%